Exploring the landscape of brand extensions: A bibliometric analysis of scholarly trends and insights - Mohit; Chaudhry, Rishi (The Scientific Temper, 2024)
This bibliometric analysis offers scholarly insights into brand extension research by examining academic output, influential sources, leading authors, and keyword co-occurrences in the field. Analyzing a dataset spanning from 2014 to 2023, the study reveals significant trends, patterns, and themes. The annual distribution of research output shows fluctuations, indicating evolving research priorities. In terms of institutional productivity, the School of Management at Zhejiang University is a leading contributor, followed closely by the Business School at Hanyang University and Dankook University, underlining their significant scholarly influence. Key sources such as the "Journal of Business Research," "Journal of Brand Management," and "Journal of Product and Brand Management" shape the discourse, emphasizing their pivotal role in brand extension exploration. Co-citation analysis identifies Keller K.L., Aaker D.A., Park C.W., and Loken B. as the most influential authors, forming the intellectual backbone of the field. Keyword co-occurrence analysis uncovers vital concepts like "brand equity," "brand management," and "perceived fit," shedding light on critical themes in brand extension research. This study enhances our understanding of brand extension literature, serving as a valuable resource for researchers and practitioners seeking to explore the evolving landscape of this dynamic field.